Discovery of a bifunctional acyltransferase responsible for ornithine lipid synthesis in Serratia proteamaculans. (7th August 2014) - Vences‐Guzmán, Miguel Ángel; Guan, Ziqiang; Escobedo‐Hinojosa, Wendy Itzel; Bermúdez‐Barrientos, José Roberto; Geiger, Otto; Sohlenkamp, Christian
Summary: Ornithine lipids (OLs) are phosphorus‐free membrane lipids that can be formed by many bacteria but that are absent from archaea and eukaryotes. A function for OLs in stress conditions and in host–bacteria interactions has been shown in some bacteria. Some bacterial species have been described that can form OLs, but lack the known genes ( ols BA ) involved in its biosynthesis, which implied the existence of a second pathway. Here we describe the bifunctional protein OlsF from S erratia proteamaculans involved in OL formation. Expression of OlsF and its homologue from F lavobacterium johnsoniae in E scherichia coli causes OL formation. Deletion of OlsF in S . proteamaculans caused the absence of OL formation. Homologues of OlsF are widely distributed among γ‐, δ‐ and ε‐ P roteobacteria and in the C ytophaga ‐ F lavobacterium ‐ B acteroidetes group of bacteria, including several well‐studied pathogens for which the presence of OLs has not been suspected, such as for example V ibrio cholerae and K lebsiella pneumonia . Using genomic data, we predict that about 50% of bacterial species can form OLs.